Another Wittgensteinian response to the evolutionary argument against naturalism - Bagheri Noaparast, Zoheir (International journal for philosophy of religion, 2024)
In “The evolutionary argument against naturalism: a Wittgensteinian response,” DeVito and McNabb (Int J Philos Relig 92(2):91–98, 2022, 10.1007/s11153-022-09832-3) propose a Wittgensteinian argument against Alvin Plantinga’s evolutionary argument against naturalism. In their paper, they seek to establish symmetry between a component of Plantinga’s premise and the premise of the radical skeptic. The first premise of Plantinga’s argument assumes the possibility of doubting the reliability of our cognitive abilities. The Radical skeptic doubts we have rational grounds to refute being brains in vats. DeVito and McNaab use hinge epistemology and Pritchard’s strategy against the radical skeptic to undermine Plantinga’s premise. This paper offers an alternative argument based on hinge epistemology against Plantinga’s argument. Relying on the various types of certainties Wittgenstein discussed, I argue that some scientific facts are among our certainties and hinges. Evolution (i.e., the theory of evolution by natural selection) is a well-established scientific fact and a hinge. As a result, in Plantinga’s first premise, we have two hinges: evolution and the reliability of our cognitive abilities. I will argue that given that hinges cannot trump one another, we can have these two hinges in place, and therefore, by endorsing hinge epistemology, there is another argument that shows why Plantinga’s argument cannot undermine naturalism if one accepts evolution.